I-CONECT intervention effects on weekly time spent outside of home and social contacts among socially isolated older adults - Yu, Kexin; Wu, Chao-Yi; Silbert, Lisa C.; Kaye, Jeffrey A.; Dodge, Hiroko H. (Frontiers in Public Health, 2024)
BackgroundSocially isolated individuals tend to have less access to cognitively stimulating activities, which could adversely impact their cognitive health. The Internet-Based Conversational Engagement Clinical Trial (I-CONECT) intervention was designed to deliver online conversation sessions to socially isolated older old adults to prevent cognitive decline. The current study examined the intervention efficacy on participants’ weekly time spent out-of-home and their social interaction with family and friends.MethodsThe intervention group engaged in frequent conversations with trained interviewers via the Internet. Both intervention and control group participants received 10-min weekly phone check-in calls over 48 weeks, during which they were asked to self-report their time (in hours) spent out of home and whether they had contacted family or friends during this week (yes/no). Linear mixed-effect models for repeated measures were run for time spent out-of-home, and mixed-effect models with a logistic link for contact with family and friends. The intervention effect was modeled by including an interaction term of time (measured in weeks) and group assignments (intervention vs. control). We ran subgroup analyses for participants with normal cognition (NC) and mild cognitive impairment (MCI). All models controlled for age, sex, race, education, and the historical event of COVID-19.Results5,495 weekly records were included in the analysis. The main effect of time was statistically significant (p < 0.001), suggesting participants spent more time out of home over time. Among the participants with NC, the intervention group had a steeper increase in their time spent out-of-home (p = 0.016) compared with the control group. Among the participants with MCI, the intervention group had an increased likelihood of contacting friends over time (p = 0.001) than the control group. The intervention effect on contact with family was not significant for either the NC or MCI group.DiscussionThe I-CONECT intervention enhanced social activities among socially isolated older old participants, which could provide additional cognitive stimulation and prevent cognitive decline.